Fish-protection devices at unscreened water diversions can reduce entrainment: evidence from behavioural laboratory investigations. (15th September 2015) - Poletto, Jamilynn B.; Cocherell, Dennis E.; Mussen, Timothy D.; Ercan, Ali; Bandeh, Hossein; Kavvas, M. Levent; Cech, Joseph J.; Fangue, Nann A.
Abstract : Water diversion can pose a risk to resident or migratory fishes, but fish-protection devices that reduce the entrainment of native fishes and maintain normal diversion activities exist. Abstract : Diversion (i.e. extraction) of water from rivers and estuaries can potentially affect native wildlife populations if operation is not carefully managed. For example, open, unmodified water diversions can act as a source of injury or mortality to resident or migratory fishes from entrainment and impingement, and can cause habitat degradation and fragmentation. Fish-protection devices, such as exclusion screens, louvres or sensory deterrents, can physically or behaviourally deter fish from approaching or being entrained into water diversions. However, empirical assessment of their efficacy is often lacking or is investigated only for particular economically or culturally important fishes, such as salmonids. The Southern population of anadromous green sturgeon ( Acipenser medirostris ) is listed as threatened in California, and there is a high density of water diversions located within their native range (the Sacramento–San Joaquin watershed). Coupled with their unique physiology and behaviour compared with many other fishes native to California, the green sturgeon is susceptible to entrainment into diversions and is an ideal species with which to study the efficacy of mitigation techniques. Therefore, we investigated juvenile green sturgeon (188–202 days post-hatch) in the presence of several fish-protection devices to assess behaviour and entrainment risk. Using a large experimental flume (∼500 kl), we found that compared with an open diversion pipe (control), the addition of a trash-rack box, louvre box, or perforated cylinder on the pipe inlet all significantly reduced the proportion of fish that were entrained through the pipe ( P  = 0.03, P  = 0.028, and P  = 0.028, respectively). Likewise, these devices decreased entrainment risk during a single movement past the pipe by between 60 and 96%. These fish-protection devices should decrease the risk of fish entrainment during water-diversion activities.